Towards Understanding the Authoring Strategy and Effectiveness of Visualization Sketches - Jiang, Ruike; Liang, Yiheng; Shao, Hanning; Liu, Le; Yuan, Xiaoru (IEEE Pacific Visualization Symposium, 2024)
Animated hand-drawing sketches are a common way to communicate concepts and information. Sketches are also used to query charts, interact with visualizations, or express rough designs. However, there is little work investigating how people manually create visualization sketches and whether animated sketches can help users understand charts. We first conduct a user study that collects the sketching processes of people with visualization knowledge and then summarize the patterns in the sketch order. Based on the sketch patterns, we conduct a between-subject study to evaluate whether animated sketches can improve users' performance of visualization tasks. We discuss the results of the user study and future work on evaluating the effectiveness of animated sketches.